Gambaran Status Gizi Balita di Puskesmas Kotaraja Jayapura - Indra Harianto Rante; Agnes Supraptiwi Rahayu; Elieser Elieser; Gregorius Adista Enrico Astawa; Setiawan Efraim Beniteis Kambu (Jurnal Syntax Admiration, 2024)
In 2020, the (UNICEF) reported 45.4 million children under five were acutely malnourished, mainly in conflict and poor regions, with the highest proportion in South Asia (14.7%). Objective: This study aims to describe the nutritional status of toddlers at the Kotaraja Jayapura Health Center. Methods: This quantitative study used secondary data obtained through purposive sampling. Samples were taken from toddlers at the Kotaraja Health Center who met the inclusion and exclusion criteria. Data were analyzed using anthropometric parameters of BB/U, PB/U or TB/U, and BB/PB or BB/TB according to World Health Organization (WHO) standards. Results: A total of 784 children under five in 21 posyandu of Kotaraja Health Center were examined in January 2024. The majority of children (39.7%) were aged 0-11 months, with almost equal gender distribution. Based on BB/U, 76.6% of children were well-nourished, and based on TB/U, 81.5% were normal. Based on BB/TB, 76.3% of children had normal nutritional status, but there were also cases of stunting, wasting, and obesity. Conclusion: The majority of toddlers aged 0-59 months at the Kotaraja Jayapura Health Center in January 2024 had good nutritional status. Based on BB/U, 76.6% of children under five had good nutritional status. Based on PB/U or TB/U, 81.5% of children under five were normal, and based on BW/PB or BW/TB, 76.3% of children under five were also normal.